Examining associations between concussion history, subjectively experienced memory problems, and general health factors in older men. Issue 1 (2nd January 2023) - Van Patten, Ryan; Iverson, Grant L.
Abstract: Objective: Examine associations between subjective memory complaints (SMCs), concussion history, and cognitive, psychological, and physical health in older men from the general population. Method: Participants were 504 men aged 50–79 who were recruited using an online labor market. Participants completed a survey assessing demographics, medication history, concussion history, recent memory problems, and additional aspects of recent cognitive, mental, and physical health. Results: Men with a lifetime history of ≥3 concussions also reported a lifetime history of being prescribed medication for anxiety (46.8%), depression (43.5%), chronic pain (79.0%), and high blood pressure (66.1%). When asked about symptoms experienced over the past year and the past week, they endorsed higher rates of cognitive and mental health problems, migraines, and difficulties with sleep and fatigue. The multivariable logistic regression model for predicting mild or greater memory problems was significant, χ2(8) = 168.97, p < .001. In unadjusted analyses, significant predictors, in order of magnitude (strongest to weakest), were fatigue (odds ratio [OR] = 3.21), back or neck pain (OR = 2.28), migraines (OR = 2.11), anxiety (OR = 2.07), depression (OR = 2.04), difficulty sleeping (OR = 1.98), and concussion history (OR = 1.49). In the multivariable model, only back or neck pain (OR = 1.51, p = .004) and fatigue (OR = 1.99, p = .004) were significant predictors. Conclusions: A personal history of multiple concussions was associated with perceived memory problems, but to a lesser degree than fatigue, back or neck pain, and migraines.